Bioinspired porous organic polymer-functionalized membranes for efficient CO2 capture. Issue 3 (13th December 2019) - Wang, Zhen; Zhang, Yiming; Wang, Jing; Zhang, Yatao
Abstract : Biomimetic enzyme loaded on porous organic polymers has used to develop mixed matrix membranes for efficient CO2 capture. Abstract : Carbonic anhydrase (CA) shows a strong affinity for CO2 and is, therefore, widely used in separation membranes for CO2 capture. Herein, a novel biomimetic material (Co-BBP) that can mimic the active site of CA was successfully synthesized and loaded on the surface of porous organic polymers (POPs). Mixed matrix membranes (MMMs) were then manufactured by incorporating Co-BBP@POP-1 nano-composites into the Pebax matrix to improve the CO2 separation performance. Compared with the MMMs doped with Co-BBP or POP-1, the prepared MMMs doped with Co-BBP@POP-1 showed exceptional CO2 separation performance owing to their synergistic effect. The MMMs containing 5 wt% of Co-BBP@POP-1 showed the optimum state with CO2 permeability of 886 Barrer and CO2 /N2 selectivity of 94.2, which surpassed the Robeson upper bound (2008). Compared with the observations for the pristine Pebax membrane, the CO2 permeability and CO2 /N2 selectivity of MMMs increased by 9.5 times and 3 times, respectively. In short, the combination of Co-BBP and POP-1 provides a good method for the application of biomimetic enzymes and may expand the synergistic effect strategy for preparing biomimetic membranes for CO2 capture.